Determinants of transition across the spectrum of alcohol use and misuse in Nigeria (2013)
Many studies have examined the risk factors associated with alcohol use disorders. No information is available from developing countries about the factors that may determine the transitions across different levels of use and misuse. Alcohol use and its misuse were assessed in a cohort of 2143 Nigerians using Version 3.0 of the World Health Organization Composite International Diagnostic Interview (WHO-CIDI). This generated six levels of alcohol use and related disorders. Using age of onset variables created for the purpose, analysis was done to determine rates of and risk factor for transition between the levels. Lifetime prevalence estimates were 57.8% for alcohol use, 27.6% for regular use, 2.9% for abuse, and 0.3% for dependence. Whereas 47.8% transited to regular use from lifetime ever use, only 10.5% transited to abuse from regular use and 9.5% from abuse to dependence. Male sex, age 18e49 years and being never married predicted onset of alcohol use. Transition to regular use was predicted only by male sex while transition to abuse was predicted by male sex and age 35e49 years. Factors associated with recovery from abuse were female sex and a student status. Higher rates of transition occurred in the stages preceding the onset of alcohol use disorders. Sex and age were the main determinants of transition, with male gender and middle age being risk factors for transition to problematic use of alcohol.